Integrated technique of buffalo fertility management in Nepal - Bhuminand Devkota; Shatrughan Shah; Gokarna Gautam (Revista Científica)
Water buffalo (Bubalus bubalis) in Nepal contributes 57% of the total milk and 36% of the total meat production in the country. Even though the buffalo farming systems range from large-scale and semi-intensive, with herd sizes of more than 50 animals, to small-scale, intensive systems in which farmers keep 1 to 5 animals, while large-scale farms are very few, and medium and small-scale farms predominate in the country. The productive efficiency of Nepalese buffaloes is relatively low, due mainly to subfertility and infertility. Delayed puberty and prolonged inter-calving intervals, attributed mainly to anestrus due to silent cyclicity and ovarian acyclicity, are the major forms of infertility in Nepalese buffaloes. Moreover, buffaloes in Nepal show a distinct seasonal breeding pattern, with July to December as the active breeding season and April to June and January to March as the low and transitional breeding seasons, respectively. It is understood that acyclicity with inactive ovaries is a major problem during the transition and low breeding season; however, silent cyclicity is expected during the good seasons. Among several factors compromising the treatment response of anestrus buffaloes in terms of pregnancy outcome, poor body condition score, sub-normal levels of some blood metabolic parameters, and gastrointestinal parasitic infection are more common. Putting together all those information, we developed an integrated technique of buffalo fertility management that includes anthelmintic treatment at least one month prior to the initiation of specific timed artificial insemination (TAI) protocol and nutritional management by means of providing vitamin–mineral supplementation in addition to improving the roughage supply and energy-protein content in the ration soon after anthelmintic treatment until two weeks after AI. Specific TAI protocol includes Ovsynch during the good season and CIDR co-synch during the transition and low seasons, as silent ovulation during the good season and acyclicity during the other two seasons are the major causes of anestrus. The TAI is important in medium and small-scale farms as the owner is responsible for heat detection, which is challenging in buffaloes. The integrated technique has succeeded in anestrus buffaloes, particularly during the low breeding season. The broader adoption of this technique as a package of practices could be a key to improving the reproductive efficiency of buffaloes in Nepal and other countries with similar farming systems.